Parametrização e validação da quitosana no campo de força OPLS-AA para caracterizar a remoção de íons fosfato - Sousa Neto, Lourival Rodrigues de (2018)
The present work consists of the parametrization and validation of chitosan in the OPLS-AA (Optimized Potentials for Liquid Simulations all atoms) force field of force to characterize the removal of phosphate ions. The reparametrization of the chitosan in the OPLS-AA was adjusted according to parameters already validated in the literature for the GROMOS53a6 (Groningen Molecular Simulation) force field. The RESP loads were obtained using the HF (Hartree-Fock) methodology and the 6-31G * base function using the NWCHEM 5.1 program. After insertion of the topology parameters (chemical bonds, angles, dihedral angles and charges) were added in the OPLS-AA simulations were performed with chitosan in vacuum and in aqueous solution for the validation of the new topological parameters. Thus, chitosan was validated based on the energy and structural results obtained in the two systems. Then the phosphate adsorption by chitosan was modeled using molecular dynamics calculations to elucidate the interactions of the biopolymer with the ion (s). Molecular dynamics calculations showed the occurrence of dipole ion interactions of the phosphate with the hydroxyl group of chitosan. Afterwards the data were out of balance for the specific interaction between the phosphate and the interacting groups of chitosan through the medium force potential (PMF) using the Umbrella Sampling method in aqueous solution containing 1 phosphate, 1 chitosan decaner and sodium chloride In order to analyze possible molecular events ignored by molecular dynamics. The results of the application of this methodology showed that in addition to the interaction with hydroxyl (results obtained by molecular dynamics), the protonated amino groups of chitosan also formed ion-dipole interactions with the phosphate ion. Therefore, the interactions between chitosan and phosphate were characterized in the OPLS-AA force field and its potential as a phosphate ion chelator for the treatment of hyperphosphatemia was confirmed.